a)
[tex] - 3 \frac{1}{3} - ( - \frac{3}{5} ) = - \frac{10}{3} + \frac{3}{5} = - \frac{50}{15} + \frac{9}{15} = - \frac{41}{15} = - 2 \frac{11}{15} [/tex]
b)
[tex] - ( - 1 \frac{5}{6} \times ( - 0.6)) = - ( - \frac{11}{6} \times ( - \frac{6}{10} )) = - ( - \frac{11}{1} \times ( - \frac{1}{10} )) = - ( \frac{11}{10} ) = - \frac{11}{10} = - 1 \frac{1}{10} [/tex]
c)
-1 5/8 + 9 3/4 ÷ (-1,3) = -1 5/8 + 9 3/4 ÷ (-13/10) = -1 5/8 + 39/4 × (-10/13) = -1 5/8 - 390/52 = -1 5/8 - 7,5 = -1 5/8 - 7 4/8 = -8 9/8 = -9 1/8
Myślę że pomogłem ;)